Singapore’s Development History: Strategy, Leadership, and Transformation toward a Developed Nation - Rindiani Kumala Putri; Mey Winda Manik; Yuliana Imel Wans Stevia; Pini Yuliani Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the historical trajectory of Singapore’s transformation from a vulnerable post-colonial island into a global economic powerhouse. The purpose of this research is to analyze the strategic development models, leadership dynamics, and structural modernizations that drove this rapid evolution. Utilizing a qualitative historical method with a literature review approach, this study synthesizes academic sources and empirical data concerning Singapore’s socio-political development. The findings reveal that Singapore’s success was anchored in the decisive and pragmatic leadership of Lee Kuan Yew, which established a highly disciplined political system, strict anti-corruption governance through meritocracy, and a strong rule of law. To overcome severe resource limitations and high post-independence unemployment, the government implemented state capitalism through export-oriented industrialization, heavily attracting multinational corporations via open market policies and business incentives. Furthermore, long-term sustainability was secured through massive public investments in a knowledge-based economy, global-standard education, vertically integrated urban planning (smart nation), and innovative water infrastructure. These systemic transformations eventually generated profound sociological shifts, fostering a highly rational, professional, and technology-adaptive contemporary society. In conclusion, Singapore’s rise demonstrates how strategic policy integration, institutional integrity, and human capital development can effectively overcome physical and geopolitical vulnerabilities to achieve first-world status.